Retraction Note to "Emitter Clogging and Hydraulic Performance of Drip System under Different Water Qualities and Placement Techniques" [Food Science and Engineering, Volume 2 Issue 2 (2021), 112-125] - Universal Wiser Publisher (Food Science and Engineering, 2025)
The Editor-in-Chief and the Editorial Office of Food Science and Engineering (FSE) have retracted the following article: Singh D, Patel N, Singh N, Rosin K, Yadav D, Singh S, Kumar Gupta A, Kumawat A, Kumar Sharma V, Kumar M. Emitter Clogging and Hydraulic Performance of Drip System under Different Water Qualities and Placement Techniques. Food Science and Engineering. 2021; 2(2): 112-125. Following a journal-wide investigation, it was identified that this article falls outside the scope of the journal and does not align with the thematic focus or subject matter requirements as outlined by the journal’s editorial policies. The retraction is in accordance with the Committee on Publication Ethics (COPE) guidelines, ensuring the integrity of the publication record is maintained. As part of the journal’s ongoing efforts to improve the quality of publications, the editorial office will continue to rigorously conduct preliminary review and peer review to ensure that only manuscripts that align with the journal’s scope and meet the highest academic standards are published. The editorial office sincerely apologizes for any confusion or inconvenience this retraction may have caused.